Vegetation Structure and Composition of Potential Nature-based Tourist Destinations in Kalipuro-Gombengsari Village, Banyuwangi Regency - Surur, Moh Miftahus; Hakim, Luchman; Rahardi, Brian (Indonesian Journal of Applied Research (IJAR), 2025)
Vegetation was significant in developing nature tourism because it provided aesthetic value and created a cool and comfortable microclimate for visitors. This study aimed to identify the vegetation structure, composition, and diversity in five potential tourist destinations in Kalipuro-Gombengsari Village, Banyuwangi Regency. The method used was purposive sampling with a total of 20 plots, where each location consisted of 4 plots. Data were collected based on three vegetation strata: trees, poles, and shrubs. Quantitative analysis was conducted using the Shannon-Wiener diversity index (H'), the evenness index (E), and Margalef's species richness index (R). The results showed that H' values in all vegetation strata were classified as low to medium. The highest H' value in the tree stratum was 1.57, and in the pole stratum was 2.31, both found in Sumber Manis. The highest value of 2.00 in the shrub stratum was recorded in Bukit Teras Hijau Kacangan. The species with the highest importance index in the tree stratum was Cocos nucifera at 206.06%, in the pole stratum was Musa paradisiaca at 96.00%, and in the shrub stratum was Coffea canephora at 193.28%. Overall, abiotic conditions in the five locations were considered normal, with the highest air temperature recorded at 24°C, soil temperature at 27.2°C, light intensity at 1,375 lux, and soil pH at 7.8.